Gastrointestinal absorption and metabolism of apple polyphenols ex vivo by the pig intestinal mucosa in the Ussing chamber. Issue 3 (17th January 2013) - Deußer, Hannah; Rogoll, Dorothee; Scheppach, Wolfgang; Volk, Antje; Melcher, Ralph; Richling, Elke
Abstract Polyphenols contained in food have various positive effects on human health. The absorption and metabolism of polyphenols in the intestinal tract needs to be studied to estimate these effects. The Ussing chamber technique was used to investigate the transport behavior of apple polyphenols through pig small intestinal mucosa, which served as a model for human gastrointestinal mucosa. The identities and concentrations of polyphenols and their metabolites in the half‐chambers (luminal and basolateral) within an incubation period of 4 h were determined by HPLC–MS/MS and HPLC–DAD (DAD = diode‐array detection). Flux values were also measured. It was found that 5‐caffeoylquinic acid and caffeic acid were absorbed and translocated to the basolateral side (1.9 and 3.7%, respectively), but other compounds, including glycosides of phloretin and quercetin, were observed without translocation. A Ussing chamber utilizing pig small intestinal mucosa is a suitable model for assessing the effect of apple polyphenols on mucosal integrity and nutrition absorption across porcine mucosa.